"Big Up West London Crew": one man's journey within a UK National Health Service rap/music therapy group. (1st June 2016) - Short, Helen; Thomas, Daniel
Abstract : Background : This paper describes work undertaken within an NHS early intervention service (EIS), incorporating the therapeutic use of original Rap, primarily focussing on one individual who formed part of a group for clients in the community. Objective : To detail the role of this specific form of therapy as part of an NHS early intervention service and demonstrate the rationale for the use of an empowerment-based model of working combined with a psychodynamic approach. Methods : The case study examines the work from a psychodynamic perspective, reframing traditional ideas within the context of the stylistic and cultural characteristics of the rap genre and highlighting their relevance when using electronic equipment and synthesised music. Discussion : Original lyrics and therapeutic techniques specific to the client are drawn upon and discussed. The author also reflects upon the use of a combination of several therapeutic models as related to the current music therapy landscape. Conclusions : The case material highlights the way in which one client was able to utilise rap-based therapy work within the musical-therapeutic relationship and the value of the properties of the rap form as a therapeutic intervention.